A importância do processo de alfabetização, letramento e numeramento no laboratório– CALENU- município de Arraias-TO - PINHEIRO, Taianara dos Santos (Universidade Federal do Tocantins, 2025)
Being literate is one of the most important skills a person can develop. Literacy one of the factors of the subject to engage with language to understand and talk about meanings in all aspects: reading, writing, interpreting and listening. In the case of this research, the proposed investigation aimed to analyze the processes of literacy, literacy and numeracy, verifying the perception of students and coordinators who work at the Literacy Center for Literacy and Numeration - CALENU when attending school students. This Center is considered a training laboratory space that serves elementary school students from 1st to 5th year with learning difficulties, enrolled in the Municipal Center for Basic Education - CMEB Professora Lívia Lorene Bueno Maia, located in Stingrays/TO. This research was based on the principles of the qualitative research approach. The authors who helped in the reasoning were: Diogo; Gorette (2011), Soares (2004), Faria (2007), Goulart (2006), Leão (2015), among others. The research participants were 5 (five) students from UFT Campus de Arraias from the Rural Education, Mathematics and Pedagogy courses who worked on the project in the year 2018-2019 and 3 (three) coordinators who also work directly in the pedagogical organization of the project. Through this research, it was possible to verify as a result that CALENU: contributes to the students' learning, corroborates to give meaning to the contents and motivates learning; complement what children cannot learn in regular school; in addition to teaching literacy, encouraging literacy, self-esteem, self-confidence and overcoming difficulties. Being highly important for everyone involved, whether they are students, coordinators, students, family and community.